Legal Requirements and Appointment Procedures for Cooperative Deed Notaries: Evidence from Malang - Fajar Tri Setiadi; Herlindah; Herman Suryokumoro (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
This study examines the implementation of regulations regarding the requirements and appointment procedures for Notaries as Makers of Cooperative Deeds (NPAK) in the drafting of Cooperative Establishment Deeds in Malang City. NPAKs hold a vital position as public officials authorized to draft cooperative deeds ; however, in practice, various regulatory and operational obstacles are still encountered in the field. This research focuses on three main aspects: the implementation mechanism of the regulations and appointment procedures for NPAKs in Malang City, the inhibiting factors faced during the implementation process, and the formulation of efforts that can be taken to overcome these existing obstacles. To address these issues, this study employs an empirical legal research method with a socio-legal approach in the Malang City region. Data were gathered directly through interview techniques and documentary studies with respondents comprising NPAKs, non-NPAK notaries, the Department of Cooperatives, and relevant professional organizations, which were subsequently analyzed using a descriptive-qualitative method. The results indicate that the implementation of the regulations has generally proceeded in accordance with the applicable administrative criteria , but its execution remains suboptimal due to differing interpretations of the procedures and the uneven participation of notaries. This suboptimality is driven by both juridical and non-juridical obstacles , which require refined harmonization among ministries and continuous legal education for the public .